Factors of individual preference towards adult care centre: a study at VADs Company Berhad / Nurrul Adila Md Zin and Norhaida Md Khalid - Md Zin, Nurrul Adila; Md Khalid, Norhaida (Faculty of Business and Management, 2015)
Previous research and study has shown that the research on the preferences of the elderly for various care arrangements is scarce, since most extant research is based on the actual use of services rather than the preferences of potential users. Thus, the goal of this study is to identify the factors of individual preference towards adult care center at VADs Company Berhad in Kuala Lumpur. The study also aims to examine the relationship between adult care center and individual preference which staff attitude and behavior, care activities and environment of care. To investigate the most influencing factor of individual preference which staff attitude and behavior, care activities and environment of care towards adult care center and to know the best individual preferences which environment care, staff attitude and behavior, and social care activities towards adult care center. A sample 120 of employee was drawn from VADs Company Berhad are distribute in order to gain the data and add depth to findings from the content analysis.